The Extended Finite Element Method for Dynamic Fractures - Goangseup Zi; Hao Chen; Jingxiao Xu; Ted Belytschko (Shock and Vibration)
A method for modelling arbitrary growth of dynamic cracks without remeshing is presented. The method is based on a local partition of unity. It is combined with level sets, so that the discontinuities can be represented entirely in terms of nodal data. This leads to a simple method with clean data structures that can easily be incorporated in general purpose software. Results for a mixed-mode dynamic fracture problem are given to demonstrate the method.